The Neo-Assyrians at Tell el-Hesi: A Petrographic Study of Imitation Assyrian Palace Ware - Engstrom, Christin M. A. (Bulletin of ASOR, 2004)
The research described here was conducted to determine the geographical provenance of selected imitation Assyrian Palace Ware sherds unearthed at Tell el-Hesi in strata of the eighth and seventh centuries B. C. E. The goal was to establish if the unusually large numbers of Assyrian Palace Ware sherds found at Hesi were imported from Assyria proper or "imitation" pieces manufactured at or near Hesi. To that end, selected samples of imitation Assyrian Palace Ware from Hesi were thin-sectioned and their petrographic profiles compared with samples of Assyrian Palace Ware from Khirbet Qasrij, Iraq, with the geomorphology of the region surrounding Tell Jemmeh, and with petrographic descriptions of Tell Jemmeh pottery. Data presented here indicate that the Hesi Palace Ware samples were manufactured local to Hesi in the loess depositional region of the Beersheva basin.